Some Integrals involving generalized hypergeometric function (2008)
Recently Virchenko and collaborators discussed a generalization of the function (see article pdf) where 2R1 (a, b; c;; x) is the generalized hypergeometric function presented by Dotsenko in 1991. The purpose of this article is to obtain some results that involve cases specials of this function and obtain computable forms for them.